Salt-Induced Vesicle Formation from Single Anionic Surfactant SDBS and Its Mixture with LSB in Aqueous Solution - Zhai, Limin; Zhao, Mei; Sun, Dejun; Hao, Jingcheng; Zhang, Lungjun (The journal of physical chemistry. B, 2005)
Vesicles can be formed spontaneously in aqueous solution of a single anionic surfactant sodium dodecyl benzenesulfonate (SDBS) just under the inducement of salt, which makes the formation of vesicle much easier and simpler. The existence of vesicles was demonstrated by TEM image using the negative-staining method. The mechanism of the formation may be attributed to the compression of salt on the electric bilayer of the surfactant headgroups, which alters the packing parameter of the surfactant. The addition of the zwitterionic surfactant lauryl sulfonate betaine (LSB) makes the vesicles more stable, expands the range of formation and vesicle size, and reduces the polydispersity of the vesicles. The vesicle region was presented in a pseudoternary diagram of SDBS/LSB/brine. The variations of vesicle size with the salinity and mixing ratios, as well as the surfactant concentration, were determined using the dynamic light scattering method. It is found that the vesicle size is independent of the surfactant concentration but subject to the salinity and the mixing ratio of the two surfactants.